Arming the Irish Revolution : gunrunning and arms smuggling in Ireland, 1911-1922 - Kautt, William H. (William Henry), 1968- (Modern war studies., 2021)
"Supply is so critical to warfighting that armies win and lose wars over it. In Arming the Irish Revolution, W.H. Kautt uses the complicated history of Ireland's revolution as a backdrop to examine in detail how the Irish rebels acquired their weapons to fight the most powerful army in the world and, ultimately, to obtain their independence. While there are studies that examine various elements of issues and topics surrounding arms acquisition during this period, none has done so comprehensively, or as more than just a backdrop to another topic. As a result, there has been no assessment of these activities or their influences on the outcomes of the war. The republican movement in Ireland created and kept a considerable number of documents, which have survived and are now available to researchers. Within those pages is the story of the movement's successes and failures, a story that Kautt brings to life in this book"--